LIVER FUNCTION TESTS IN PREECLAMPSIA - Munazza, Bibi; Raza, Nuzhat; Naureen, Ayesha; Khan, Shahbaz Ali; Fatima, Fozia; Ayub, Muhammad; Sulaman, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Preeclampsia is a multisystem disorder that can induce damage to cardiovascular system, kidneys, brain and liver. Pregnancy-induced hypertension (PIH) is responsible for significant maternal and perinatal morbidity. This study was conducted to compare the liver function tests in preeclampsia with normal pregnancy. Methods: This study was carried out on 100 pregnant women after 20 weeks of gestation admitted in Obs/Gyn units of Ayub Teaching Hospital, Abbottabad. The subjects were divided into two groups. Group A consisted of 50 cases of preeclampsia having blood pressure ï‚³140/90 mmHg, proteinuria in 24 hours ï‚³300 mg and oedema; Group B had 50 normal pregnant women after 20 weeks of gestation. The data including BMI, parity, period of gestation, blood pressure and presenting complaints of all subjects were recorded. Serum bilirubin and plasma levels of liver enzymes ALT, AST and ALK were measured. Results: The mean BMI of the cases was 29.04±3.97 and that of controls was 26.54±3.11. The mean value of serum bilirubin in cases was 10.78±3.74 µmol/L and in controls it was 7.92±2.42 µmol/L (p<0.001). The mean values of enzyme ALT in cases was 55.81±31.93 U/L while in the controls it was 15.22±3.30 U/L (p<0.001). Mean serum AST in the cases was 41.34±10.76 U/L and in the controls it was 24±2.54 U/L (p<0.001). Mean ALK level of cases before delivery was 454.16±243.69 U/L, and in controls it was 181.34±66.76 U/L (p<0.001). Conclusion: Raised levels of serum bilirubin and liver enzymes ALT, AST and ALK were found in preeclampsia cases. Keyword: Preeclampsia, Liver Function Tests, Pregnancy, Hypertension, Morbidity, Women